1992
DOI: 10.1097/00006123-199206000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Osteolytic Malignant Meningiomas Appearing as Extracranial Soft-Tissue Masses

Abstract: Malignancy is rare in intracranial meningiomas. Although the topic is widely discussed, there is little agreement in the literature as to the histological and radiological features that warrant the diagnosis of malignant meningioma. Three patients are described who had soft-tissue masses and underlying osteolytic lesions on computed tomography. All three patients also had a large intracranial component that proved to be a malignant meningioma. Rarely do meningiomas have all three of these features. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Although they are benign lesions, recent studies emphasize that intraosseous meningiomas have a higher incidence of malignant characteristics compared to intradural meningiomas [5,6]. The typical findings were found to be compatible with a meningothelial meningioma in our case.…”
Section: Discussionsupporting
confidence: 63%
“…Although they are benign lesions, recent studies emphasize that intraosseous meningiomas have a higher incidence of malignant characteristics compared to intradural meningiomas [5,6]. The typical findings were found to be compatible with a meningothelial meningioma in our case.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies indicate that intraosseous meningiomas have a higher incidence of malignant features than intradural meningiomas have7,14,17). One report reviewed 65 published cases of intraosseous meningioma, assessed during the CT era, and found that 17 (26%) had atypical or malignant histological features10).…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas causing osteolysis and soft-tissue extension should be considered malignant. 14) We treated our patient with fractionated radiotherapy. The long-term outcome in such cases is unclear.…”
Section: Discussionmentioning
confidence: 99%